Analysis of genetic diversity of bacteria Xanthomonas oryzae pv. oryzae causes leaf blight in North Sumatra - Zulheri Noer; Maimunah Maimunah; Erwin Pane; Eko Prasetya (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Xanthomonas oryzae pv. oryzae (Xoo) causes bacterial leaf blight on rice plants, which is responsible for crop failure, resulting in economic losses. Control of Xoo bacteria can be accomplished through the use of Xoo-resistant rice varieties. Due to the shifting genetic structure and environmental conditions of Xoo bacteria, it is difficult to identify them according to their pathotype. This study aims to determine the genetic diversity of Xoo bacteria using the polymerase chain reaction (PCR) method and the IS1112-based RAPD marker, which is known to contain repetitive sequences. DNA was isolated from 52 isolates collected from 15 districts and cities in North Sumatra province and then used to amplify the IS1112 sequence. Dendrogram analysis revealed that cluster analysis of PCR findings classified isolates into 15 groups with a 90% similarity value. Genetic variation among Xoo isolates from North Sumatra ranged between 51% and 100%. North Sumatra Xoo isolates exhibited a high degree of genetic diversity. This findings can be used as a resource for future management of the Xoo bacteria by expediting disease-resistant rice breeding projects in various rice producing countries.